Pengaruh Ukuran Perusahaan, Likuiditas, Konservatisme, Dan Pertumbuhan Laba terhadap Kualitas Laba - Puspitasari, Dilla Amalia; Pramono, Hadi; Santoso, Suryo Budi; Kusbandiyah, Ani (Universitas Batanghari, 2024)
The purpose of this study is to determine how firm size, liquidity, conservatism, and earnings growth affect earnings quality as the firm grows. Property and real estate manufacturing companies listed on the Indonesia Stock Exchange from 2019-2021 are the subject of this study. Using purposive sampling method, a sample of 48 companies listed on the Indonesia Stock Exchange was selected. The data was tested with multiple linear regression. This study shows that company age has a positive effect on earnings quality as a control variable, liquidity has a positive effect on earnings quality, conservatism has a negative effect on earnings quality, and company size has a negative effect on earnings quality.